Biogranulation technology for the treatment of anaerobically digested palm oil mill effluent using sequencing batch reactor - Nuid, Maria (2020)
Ponding treatment system has been widely used to treat palm oil mill effluent (POME) due to its low operating cost and ease of operation. However, it has some disadvantages such as requirement for a large area, long hydraulic retention time (HRT), and emittance of bad odour. Biogranulation system tested on different types of wastewater offers a solution for the problems. Although this system has been tested for different types of POME, its application in treating anaerobically digested POME has not been previously explored. Therefore, this study was conducted mainly to investigate the feasibility of biogranulation system for treatment of anaerobically digested POME. This study was carried out using a laboratory-scale sequencing batch reactor (SBR) under intermittent anaerobic and aerobic conditions with a working volume of 2 L. Serratia marcescens SA30 (SMSA30) strain was added to the system to treat high concentration of oil and grease (O&G) in wastewater. The system was operated with the variable organic loading rates (OLR) of 0.69 to 9.90 (kg/m3 d), HRT of 4 to 24 h, and superficial air velocity (SAV) of 2 cm/s. After 60 days addition of SMSA30 strain, the flocculent biomass was transformed into biogranules with excellent settleability with improvement in treatment efficiency of the system. Stable biogranules with an average diameter of about 2 mm, sludge volume index (SVI) of 43 mL/g and settling velocity of 81 m/h, were obtained in the biogranular system following 256 days of operation. Upon the biogranules formation, the average removal efficiencies of total chemical oxygen demand (CODT), soluble chemical oxygen demand (CODS), total nitrogen (TN), total phosphorous (TP) and O&G increased from 19 to 52%, 24 to 61%, 51 to 88% and 65 to 84% and 6 to 99.92%, respectively. The results also show that the HRT, OLR and food to microorganism (F/M) ratio influenced the removal efficiency. The removal efficiency of COD, TN, TP and O&G improved with increase in HRT; the percentage of COD and TP removal were slightly increased with the increase of OLR and F/M ratio. By contrast, the removal of TN and O&G was reduced with the increase of the OLR and F/M ratio. The modified mass transfer factor (MMTF) models were used to scrutinise the mechanisms of mass transfer for the biosorption of organic matter and nutrient i.e., CODT and CODS, TN and TP, accumulated onto biogranules. The application of MMTF models verified that resistance of mass transfer is dependent on the film mass transfer for the biosorption of CODT, CODS, TN, and TP. The performance of the biogranular system would increase with increase in global mass transfer factor ([kLa]g) value and thus, provides a new insight in the dynamic response of aerobic digestion to biogranules development. This study demonstrates that the biogranular system, with addition of SMSA30 is feasible for treatment of anaerobically digested POME.